Digital Formative Assessment Strategies in Blended Learning Contexts: A Qualitative Case Study - Morovvati, Sara (Assessment and Practice in Educational Sciences, 2024)
This study aimed to explore the strategies employed by educators to implement digital formative assessment in blended learning contexts, focusing on pedagogical intentions, technological affordances, and professional practices. A qualitative case study design was utilized, involving semi-structured interviews with 26 educators from secondary and post-secondary institutions in Tehran who have experience with blended learning. Participants were selected through purposive sampling to ensure diversity in subject areas and teaching backgrounds. Data collection continued until theoretical saturation was achieved. All interviews were transcribed verbatim and analyzed using thematic analysis, supported by Nvivo software to code, organize, and identify patterns in the data. Three main themes emerged from the analysis: (1) Pedagogical Intentions and Design, emphasizing the alignment of assessments with learning objectives, differentiation, timely feedback, integration within instructional cycles, and scaffolding for metacognition; (2) Digital Tools and Technological Affordances, highlighting the importance of platform functionality, interactive features, data analytics, accessibility, and tool selection criteria; and (3) Teacher Beliefs and Professional Practices, including attitudes towards digital assessment, assessment literacy, peer collaboration, implementation challenges, and ethical considerations. Teachers recognized digital assessment as enhancing personalization, engagement, and feedback timeliness but also identified challenges such as technological limitations and equity concerns.Digital formative assessment strategies in blended learning environments present significant opportunities for supporting student learning, fostering metacognitive skills, and providing timely, actionable feedback. However, effective implementation requires careful alignment with pedagogical objectives, attention to accessibility and ethical concerns, and robust professional development for educators. Addressing persistent challenges in technology and equity will be critical for maximizing the potential of digital formative assessment.